ANALYSIS OF FACTORS ASSOCIATED WITH COMPLETENESS OF BASIC IMMUNIZATION IN BABIES AT THE BANDA RAYA COMMUNITY HEALTH CENTER, KOTA BANDA ACEH IN 2021 - Syawaluddin, Syawaluddin; Arbi, Anwar; Santi, Tahara Dilla (Jukema (Jurnal Kesehatan Masyarakat Aceh), 2024)
Background: Complete basic immunization coverage at the Banda Raya Community Health Center is 67.6%. Low levels of complete basic immunization in babies must be addressed immediately so that children can grow and develop healthily and avoid infectious diseases. This study aims to analyze the completeness of basic immunization for babies at the Banda Raya Community Health Center, Banda Aceh City in 2021. Method:This research is descriptive analytical with a crosssectional design. The sample was 63 patients determined using total population techniques. Data analysis used the Chi-Square test with SPSS version 20. Result: there was a relationship between knowledge (p-value=0.016), parental education (p-valu=0.006), the role of cadres (p-valu=0.040), the role of health workers (p-value0.001), family support (p-value=0.023), and maternal motivation (p-value=0.013) with complete basic immunization for babies at the Banda Raya Community Health Center, Banda Aceh City in 2021. Recommendation: It is hoped that health workers can carry out health promotion, especially community promotion emphasizing the consequences if children are not given basic immunizations, one of which is by socializing the importance of proper immunization according to a predetermined schedule.